Errors of Diagnosis in Pediatric Practice: A Multi-Site Survey - Singh, Hardeep (2010)
OBJECTIVES: Despite their significance, little is known about diagnostic errors in general pediatric practice other than data from malpractice claims. We surveyed pediatricians to elicit their perceptions about frequency, contributing factors and potential systems and provider-based solutions to address diagnostic errors. METHODS: Academic, community, and trainee pediatricians at three tertiary care institutions and affiliated 109 clinics (N=1,362) were invited to complete the survey anonymously via an Internet survey administration service between November 2008 and May 2009. RESULTS: Overall response rate was 53% (N=726). Over half (54%) of respondents reported that they made a diagnostic error at least once or twice per month; this frequency was markedly higher (77%) among trainees. Almost half (45%) reported diagnostic errors that harmed patients at least once or twice per year. Failure to gather information through history, physical examination or chart-review was the most common reported process breakdown, whereas inadequate care coordination and teamwork was the most common system factor reported. Viral illnesses being diagnosed as a bacterial illness was the most commonly reported diagnostic error followed by misdiagnosis of medication side-effects, psychiatric disorders, and appendicitis. Physicians ranked access to electronic health records and close follow-up of patients as strategies most likely to be effective in preventing diagnostic errors. CONCLUSIONS: Pediatricians reported making diagnostic errors relatively frequently and patient harm from these errors was not uncommon. Our survey provides new data about the types of diagnostic errors and their causes and lays the groundwork for a concerted, multifaceted approach to reduce these errors in children.